External negative pressure improves lung aeration in near-term rabbit kittens at risk of developing respiratory distress - Diedericks, C.; Crossley, K. J.; Jurkschat, D.; Wallace, M. J.; Davies, I. M.; Riddington, P. J.; te Pas, A. B.; Kitchen, M. J.; Hooper, S. B. (Frontiers in Pediatrics, 2025)
IntroductionAs airway liquid is cleared into lung interstitial tissue after birth, the chest wall must expand to accommodate this liquid and the incoming air. We examined the effect of applying external positive and negative pressures to the chest wall on lung aeration in near-term rabbit kittens at risk of developing respiratory distress.MethodsRabbit kittens (30 days; term ∼31 days) were randomised into Control and Elevated Liquid (EL) groups. Lung liquid was drained in Control kittens to simulate expected volumes following vaginal delivery. EL kittens had lung liquid drained before 30 ml/kg was returned to simulate expected volumes after caesarean section. Kittens were delivered, placed in a water-filled plethysmograph and the external pressure was adjusted to −6 (negative), 0 (atmospheric), or +6 (positive) cmH2O. Kittens were ventilated with an 8 ml/kg tidal volume and PEEP of 0 cmH2O and lungs imaged using phase contrast x-ray imaging.ResultsCompared to external atmospheric pressures, external negative pressures expanded the chest (by 2100 ± 43 vs. 1805 ± 59 mm2; Control kittens; P = 0.028), directed tidal ventilation into lower, larger lung regions and increased functional residual capacity (FRC) levels in both Control (26.7 ± 2.0 vs. 12.6 ± 2.2 ml/kg; P < 0.001) and EL (19.6 ± 1.6 vs. 10.0 ± 2.9 ml/kg; P < 0.01) kittens. External positive pressures reduced FRC levels in Control (6.3 ± 0.8 vs. 12.6 ± 2.2 ml/kg; P < 0.05), but not in EL kittens, and directed tidal ventilation into upper lung regions.DiscussionExternal negative pressures increased lung aeration and resulted in a more evenly distributed tidal ventilation immediately after birth in near-term rabbit kittens, whereas external positive pressures reduced lung aeration and compliance.